Ranljivost gozdnih tal in vrednotenje hidrološke ter varovalne vloge gozdov v Mestni občini Ljubljana - Planinšek, Špela (Gozdarski vestnik, 2010)
An important share of the forest soil (25%) in the Municipality of Ljubljana is mapped as water protection area; therefore we assume that the forest soil condition and forest ecosystems preservation directly affect the quantity and quality of water sources. Similar conclusions were also drawn by many nationaland foreign studies of water circulation in forest space. Therefore, forest cove is not only water consumer; it is also its natural filter and storage. The vulnerability of forest soil, which can, due to the erosion, be shown also as the pollution of drinking water sources, were presented through matrix modeling in our study. In the model, we evaluated the needs for the hydrological and protection role of the forest, reflected by the external - ecological factors (slope of the terrain and soil types with regard to their erodibility and drainage). The synthetic map represents an objective basis fo rplanning forest management and silvicultural measures with which we can improve the forest's capability for ensuring its hydrological and protection role. The results of the model represent the first step toward a different understanding of determination of forest's functional units and can be used as information on the most vulnerable areas (22% of forest soil), which are dueto the steep slope or intense ground porousness subject to the erosional processes. These can be mitigated or even nullified by the application of appropriate forest management measures. Set of measures for two extreme areas with regard to growing site is one of the results of this study.
Keywords: Ljubljana City Municipality; Mestna občina Ljubljana; Ljubljana; gozdne površine; forest; gozd; vrednotenje; hidrološka vloga; varovalna vloga